LDAP in the Solaris operating environment : deploying secure directory services - Haines, Michael (Sun blueprints., 2004)
LDAP in the Solaris Operating Environment Deploying Secure Directory Services Provides an in-depth discussion of Solaris Operating Environment security methods and how they relate to LDAP as a naming service Covers migration planning tips from NIS/NIS+ to an LDAP-based naming service including capacity planning Presents an overview of LDAP tools and toolkits, and how they are used to administer LDAP as a naming service Discusses performance principles and benchmarking techniques for optimizing directory server performance LDAP in the Solaris Operating Environment is a follow-on to the Sun BluePrints book Solaris and LDAP Naming Services, and describes the significant improvements to the Solaris LDAP client and directory server. Deploying the Solaris Secured LDAP Client is covered in detail. This Sun BluePrints book introduces NIS/NIS+ migration tools and techniques to aid in the transition to an LDAP-based naming service. Troubleshooting tips, examples of extending Solaris authentication methods, and examples of extending Solaris authentication methods using the Pluggable Authentication Module (PAM) framework are provided.